2006
DOI: 10.1097/01.blo.0000238874.09390.a1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Obesity on Stability Following Revision Total Hip Arthroplasty

Abstract: Similar outcomes have been reported for obese and nonobese patients after primary total hip arthroplasty (THA), indicating obesity is not a contraindication to total hip arthroplasty. However, obese patients may develop implant failure and require revision THA. We compared the outcomes of revision THA in a matched cohort of obese and nonobese patients. Patients were stratified into two groups according to BMI (body mass index, kg/m2): Group 1 included 31 obese patients (BMI > 35), and Group 2 included 62 nonob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 23 publications
6
44
1
Order By: Relevance
“…In a recently published study on patients undergoing hip revision arthroplasty, the risk of implant dislocation was 6 times higher in obese patients than in non-obese patients (Kim et al 2006). These two results support the hypothesis that high BMI is an important risk factor for implant dislocation.…”
Section: Discussionsupporting
confidence: 76%
“…In a recently published study on patients undergoing hip revision arthroplasty, the risk of implant dislocation was 6 times higher in obese patients than in non-obese patients (Kim et al 2006). These two results support the hypothesis that high BMI is an important risk factor for implant dislocation.…”
Section: Discussionsupporting
confidence: 76%
“…The authors also defined obesity as a BMI of greater than 35 kg/m 2 and nonobese as less than 30 kg/m 2 . Patients in between these two values were not included in the study [7]. Another study of 229 patients by Perka et al [13] reported overweight patients had an increased operative time in revision hip surgery but no other increase in perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by the data of McClung et al [9] who quantified the daily activity level of 209 patients with a pedometer and found obese patients were less active. Kim et al [7] studied the outcomes of revision hip arthroplasties of nonobese versus obese patients. They reported obese patients were six times more likely to sustain dislocations than nonobese patients, and obese patients were two times more likely to undergo repeat revision surgery than nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
“…When obesity is defined as a body mass index (BMI) greater than 30 kg/m 2 in adults, obesity is recognized as an independent risk factor for postoperative hip dislocation in several studies [2,6,8,15,18,22,28,35]. However, in these patients with obesity, it is not known whether the risk is only in the early postoperative period or if the risk persists several years after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…All yearly postsurgery weight outcomes were compared with the presurgery weight with the BMI index. Because thigh impingement is one cause of dislocation [14,18], and because we have noted that after bariatric surgery some patients had a decrease in BMI without resolution of thigh impingement, we also measured (Fig. 3) thigh circumference and hip circumference (Table 2), which are parameters [16,20,25] of the body adiposity index (BAI) [3], an alternative measure of body fat.…”
Section: Evaluation Of Obesitymentioning
confidence: 99%